2004
DOI: 10.1007/s00125-004-1585-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of type 2 diabetes on various electrophoretic characteristics of low-density lipoprotein particles in women

Abstract: Aims/hypothesis. Coronary heart disease represents the leading cause of death in type 2 diabetic patients. As the small, dense LDL phenotype is a typical feature of the dyslipidaemic state found in type 2 diabetes, this characteristic could be an important mediator of the elevated coronary heart disease risk in this condition. We have therefore studied the effect of type 2 diabetes on various electrophoretic characteristics of LDL particles. Methods. Potential differences in LDL peak particle size and in conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Plasma cholesterol concentrations of LDL subclasses have been approximated by multiplying the percent areas of Sudan black-stained gels by plasma LDL cholesterol [119,129]. Based on published [130][131][132] and personal observations, Rainwater and colleagues [133] argue that when the gels are stained with Sudan black, absorbance profiles reflect the cholesterol distribution among LDL subclasses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma cholesterol concentrations of LDL subclasses have been approximated by multiplying the percent areas of Sudan black-stained gels by plasma LDL cholesterol [119,129]. Based on published [130][131][132] and personal observations, Rainwater and colleagues [133] argue that when the gels are stained with Sudan black, absorbance profiles reflect the cholesterol distribution among LDL subclasses.…”
Section: Discussionmentioning
confidence: 99%
“…Haffner and colleagues [188] reported that men and women who had NIDDM had smaller LDL peak diameter than those who were nondiabetic, but when adjusted for triglycerides and HDL cholesterol concentrations, the difference persisted in women but not men. Blackburn and colleagues [129] also reported that LDL peak particle size was significantly smaller in women who had type 2 diabetes mellitus than in women who were nondiabetic, even when matched for waist circumferences and plasma triglyceride levels, and those who had diabetes had a greater proportion of their LDL cholesterol in small LDL (!25.5 nm) and a smaller proportion in large LDL (R26.0 nm) than women who did not have diabetes, despite no differences in total LDL cholesterol.…”
Section: Diabetesmentioning
confidence: 93%
“…Recently, however, evidence has emerged that other metabolic disturbances may also predispose to this pattern. Blackburn et al [27] found a lower LDL peak particle size in women with diabetes compared with control subjects even when differences in waist and plasma triglyceride were taken into account. Similarly, Veerkamp et al [28] found that subjects with familial combined hyperlipidaemia had increased levels of apolipoprotein B and more small dense LDL independent of the presence of insulin resistance and the degree of obesity.…”
Section: Epidemiologic Studies Of Small Dense Low-density Lipoproteinmentioning
confidence: 98%
“…The LDL peak particle diameter was obtained from nondenaturing 2e16% polyacrylamide gradient gel electrophoresis as previously described [30]. LDL particle size was extrapolated from the relative migration of four plasma standards of known diameters.…”
Section: Ldl Sizementioning
confidence: 99%